2022
DOI: 10.1186/s13048-022-00981-7
|View full text |Cite
|
Sign up to set email alerts
|

miR-600 promotes ovarian cancer cells stemness, proliferation and metastasis via targeting KLF9

Abstract: Previous studies have revealed that miRNAs participate in the pathogenesis of ovarian cancer; however, whether miR-600 is also involved remains unclear. In this study, we aimed to investigated the role of miR-600 in ovarian cancer progression. Here, miR-600 expression was significantly upregulated in ovarian cancer tissues and stem cells. Functional studies showed that miR-600 promoted ovarian cancer cell stemness, proliferation and metastasis. Mechanistic studies revealed that Kruppel like factor 9 (KLF9) was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Krüppel-like factor 9 (KLF9), belonging to the KLF transcriptional factor family, has been extensively investigated in tumors. For example, KLF9 was reported to play suppressing roles in multi-tumors including non-small cell lung cancer, ovarian cancer, gastric cancer [11][12][13]. As expected, KLF9 as a suppressor for HCC has been reported.…”
mentioning
confidence: 75%
“…Krüppel-like factor 9 (KLF9), belonging to the KLF transcriptional factor family, has been extensively investigated in tumors. For example, KLF9 was reported to play suppressing roles in multi-tumors including non-small cell lung cancer, ovarian cancer, gastric cancer [11][12][13]. As expected, KLF9 as a suppressor for HCC has been reported.…”
mentioning
confidence: 75%
“…In mammalian cells, it is universally acknowledged that miRNAs are at least partially complementary to the 3′‐UTR of the target mRNA molecule to mediate the target gene expression at the posttranscriptional level 26 . KLF9 belongs to the KLF transcriptional factor family, and it was reported to participate in the progression of ovarian cancer and BC 27,28 . Yang et al reported that KLF9 had lower expression in BC and was a targeted gene of miR‐17‐5p 28 .…”
Section: Discussionmentioning
confidence: 99%
“…26 KLF9 belongs to the KLF transcriptional factor family, and it was reported to participate in the progression of ovarian cancer and BC. 27,28 Yang et al reported that KLF9 had lower expression in BC and was a targeted gene of miR-17-5p. 28 In this study, we found that in BC cells, KLF9 expression was reduced consistently.…”
Section: Discussionmentioning
confidence: 99%
“…By binding to the promoter of integrin α6, KLF9 highly suppresses the integrin signaling pathway, which is detrimental to the self-renewal of CSCs ( 200 ). However, some CSCs target KLF9 by upregulating miR-600, thus rescuing this repressive effect ( 201 ).…”
Section: Implications Of Klfs In Tumor Developmentmentioning
confidence: 99%